Investigating the Influencing Factors of Teachers’ Information and Communications Technology-Integrated Teaching Behaviors toward “Learner-Centered” Reform Using Structural Equation Modeling - Jing Zhang (MDPI AG, 2021)
In the context of information-driven Education transformation, this study investigates factors that influence the continuous transformation of teacher information and communications technology (ICT) teaching methods. Although some studies have found that teacher psychological cognition exerts different effects on different types of teacher ICT-integrated teaching behaviors, the current literature on influencing factors lacks the classification of behaviors. Based on the learner-centered transformation, this study divides teacher ICT-integrated teaching behaviors into teacher-centered teaching behavior and student-centered teaching behavior, and constructs a hypothesis model of influencing factors on teacher ICT-integrated teaching behavior. We collected questionnaire data from 795 primary and secondary school teachers, then validated and adjusted the model through structural equation modeling (SEM). The social environment exerted a significant indirect impact on teacher technology application behaviors via mediation of teacher efficacy and outcome expectations. The two types of self-efficacy directly affected the student-centered ICT application behavior more than the teacher-centered ICT application behavior. The student-centered ICT application behavior exerted a significant impact on the teacher-centered ICT application behavior. This study confirms the significance of classifying teacher ICT-integrated teaching behavior and supports the transformation of learner-centered ICT-integrated teaching by improving the social environment to realize equitable and sustainable Education development.